2015
DOI: 10.1682/jrrd.2014.10.0228
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating gaze-driven power wheelchair with navigation support for persons with disabilities

Abstract: Abstract-This article describes a novel add-on for powered wheelchairs that is composed of a gaze-driven control system and a navigation support system. The add-on was tested by three users. All of the users were individuals with severe disabilities and no possibility of moving independently. The system is an add-on to a standard power wheelchair and can be customized for different levels of support according to the cognitive level, motor control, perceptual skills, and specific needs of the user. The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…These results are similar to those reported previously in a study of power wheelchair use by three users with severe disabilities. Users reported that a gaze‐controlled interface was enjoyable to use, and provided a method to preserve independence . Previous studies have integrated other input mechanisms, such as breath or EEG, to augment the sensitivity and accuracy of gaze control .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are similar to those reported previously in a study of power wheelchair use by three users with severe disabilities. Users reported that a gaze‐controlled interface was enjoyable to use, and provided a method to preserve independence . Previous studies have integrated other input mechanisms, such as breath or EEG, to augment the sensitivity and accuracy of gaze control .…”
Section: Discussionmentioning
confidence: 99%
“…Studies that counter the relationship between mobility and QOL show that social interactions and leisure activities are more important determinants of QOL than mobility . Additionally, motor control systems in commercially available power wheelchairs may have sub‐optimal UIs, which may be nonintuitive, have delayed response times, or require motor input or complex abstract cognitive processing . Our goal in developing this prototype eye‐gaze controlled wheelchair was to develop an intuitive technology which would use preserved oculomotor control, enable basic mobility tasks, and yield a favorable user experience for ALS patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that wearing additional equipment may result uncomfortable for the user and therefore it would be highly desirable to reduce the invasiveness of the technology. To this aim, other researches in this area [25] have proven that the task can also be solved adopting external devices. However, an eye-tracking system as the one used for their experiments is rather expensive, considerably reducing the affordability of a complete system especially by a private user.…”
Section: State Of Art In Wheelchair Control For Severely Impaired Usersmentioning
confidence: 99%
“…Besides requiring the use of a wearable device, electrooculography is an efficient diagnosis tool, but also in this case it may turn out to be fatiguing, and the number of commands that can be configured is somehow limited. This is the reason why we have chosen to use an external device, similarly to previous studies [25], but adopting an affordable system that can be easily configured and customized to fit the requirements of the specific application context.…”
Section: State Of Art In Wheelchair Control For Severely Impaired Usersmentioning
confidence: 99%